2014
DOI: 10.1093/aobpla/plu046
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the antioxidant capacity of halophytes to increase their cultural and economic value through saline cultivation

Abstract: Halophytes, salt-tolerant plants, are a source of valuable secondary metabolites with potential as functional foods or nutraceuticals. We are interested in finding the optimal cultivation conditions for increasing the contents of these valuable compounds. Growth conditions away from the optimum can induce stress resulting in changes in secondary metabolites. We analyzed metabolites with antioxidant capacity in seedlings and plants from different families and habitats grown under different salt concentrations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 59 publications
5
36
1
3
Order By: Relevance
“…Significant research has been conducted to establish that antioxidant defense is important for maintaining proper plant growth under different abiotic stress conditions, especially halophytes (Boestfleisch et al, 2014;Canalejo et al, 2014;Yildiztugay et al, 2014). In the same line, to see how the stress imposition and oxidative stress in two plant species (glycophytes and halophyte) affected their antioxidant metabolism and vice versa, activities of enzymatic antioxidant and levels of non-enzymatic antioxidants were measured.…”
Section: Discussionmentioning
confidence: 99%
“…Significant research has been conducted to establish that antioxidant defense is important for maintaining proper plant growth under different abiotic stress conditions, especially halophytes (Boestfleisch et al, 2014;Canalejo et al, 2014;Yildiztugay et al, 2014). In the same line, to see how the stress imposition and oxidative stress in two plant species (glycophytes and halophyte) affected their antioxidant metabolism and vice versa, activities of enzymatic antioxidant and levels of non-enzymatic antioxidants were measured.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols, such as flavonoids and anthocyanins, are another group of water-soluble antioxidants with a high ability to scavenge ROS. There are many reports of polyphenol accumulation and enhanced antioxidant ability in halophytes (Ksouri et al 2012;Boestfleisch et al 2014;Qasim et al 2017). Halophyte extracts had much higher total phenolic and flavonoid contents than non-halophytes (Qasim et al 2017;Ksouri et al 2012).…”
Section: Role Of Nonenzymatic Antioxidant Moleculesmentioning
confidence: 99%
“…It is known that content of polyphenols and other bioactive compounds in halophytes vary widely according to species, location, growing conditions and harvest season of the plants [40,41]. Boestfleisch et al [42] also demonstrated that altering the saline growing environment it is possible to increase the concentration of valuable secondary metabolites of halophytes, so as to behave like authentic large-scale natural reactors. Values are means of three replications ± standard deviation.…”
Section: Chemical Characterization Of Extracts By Uaementioning
confidence: 99%